2020
DOI: 10.1186/s12909-020-02325-9
|View full text |Cite
|
Sign up to set email alerts
|

Students’ readiness for and perception of Interprofessional learning: a cross-sectional study

Abstract: Background Several studies reported that Inter-professional Education (IPE) plays a major role in creating an effective collaborating environment in healthcare settings to achieve high-quality patient care. This study measured the College of Applied Medical Sciences (CAMS) students’ readiness for and perceptions of IPE. Methods A cross-sectional study was conducted with 232 undergraduate students in Riyadh, using a stratified random sampling method. All the undergraduate students of CAMS were included. Two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
8
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 11 publications
7
8
1
5
Order By: Relevance
“…The findings overall show medical and dental students were aware of the importance of IPE and ready to collaborate with other health professional students as reflected by a total RIPLS score 75 (maximum score 95). Thus, the study findings were similar to other studies reported from Saudi Arabia (mean score 86.8) 34 and Iran (mean score 84.2) 35 where students showed a high readiness for IPE. It is important to notice that the total score in the present study was not influenced by demographic parameters like the Saudi Arabian study wherein gender, and year of study had no association with the scores.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings overall show medical and dental students were aware of the importance of IPE and ready to collaborate with other health professional students as reflected by a total RIPLS score 75 (maximum score 95). Thus, the study findings were similar to other studies reported from Saudi Arabia (mean score 86.8) 34 and Iran (mean score 84.2) 35 where students showed a high readiness for IPE. It is important to notice that the total score in the present study was not influenced by demographic parameters like the Saudi Arabian study wherein gender, and year of study had no association with the scores.…”
Section: Discussionsupporting
confidence: 90%
“…It is important to notice that the total score in the present study was not influenced by demographic parameters like the Saudi Arabian study wherein gender, and year of study had no association with the scores. 34 …”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings of previous studies that suggest the need for IPE for collaborative teamwork and to cultivate roles and responsibilities to undergraduate students in medicine, nursing, pharmacy, 34 and other allied healthcare programs (eg, clinical laboratory science and physiotherapy). 6 , 34 Regarding the timing for starting IPE, most students indicated the fourth academic year; however, no existing evidence indicates the right time for health professionals to begin IPE. Berger-Estilita et al 35 reported that a third of medical students indicated that IPE should start just before or during clinical training, while another third indicated that IPE should start as early as the first year of undergraduate education and training.…”
Section: Discussionmentioning
confidence: 99%
“…The Readiness for Interprofessional Learning Scale (RIPLS), 22 Interdisciplinary Education Perception Scale (IEPS), 23 and Interprofessional Education Collaborative (IPEC) Competency Self-Assessment Scale 24 were validated, published in English, and licensed for public use. 6 Specifically, the RIPLS was validated with Korean students in nursing, medicine, and other allied healthcare professions, such as physiotherapy, occupational therapy, and dental hygiene by Lee et al, 25 and it was also used to measure the effectiveness of IPE for medical and nursing students. 26…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation